Solidification/stabilisation treatment of spiked sembrong river sediments using cement and rice husk ash - Aliyu, Mohammed Kabir (2015)
Contaminated sediment represents a significant problem for the public health as well as the environment. Solidification/Stabilisation (S/S) remediation technique was employed in this study to treat river sediment spiked with three heavy metals. The main objective of this research was to study the effect of replacing cement with rice husk ash (RHA) on compressive strength and leaching of Pb, Cr and Cu from the stabilised sediments. Artificially contaminated sediments were prepared by individually spiking each sediment sample with solutions of Lead nitrate (Pb(NO3)2), Copper sulphate (CuSO4.5H2O) and Potassium dichromate (K2Cr2O7) to achieve an average of 1000 ppm target concentration of each element. Cement was added at 10% and rice husk ash at 5, 10 15 and 20% throughout to the total dry weight of mixture, which were then cured at room temperature (27 ± 3oC) and humidity of 75 ± 5 % for 7, 14 and 28 days. Cylindrical samples were prepared with water - cement ratio of 0.4. The effectiveness of the treatment was evaluated by performing unconfined compressive strength (UCS) test on compacted samples and three different leaching tests, namely Toxicity Characteristic Leaching Procedure (TCLP), Synthetic Precipitation Leaching Procedure (SPLP) and Deionized Water Leaching tests (DIW) at curing periods of 7, 14 and 28 days. X-ray diffraction (XRD) analysis was used to study the reaction products and crystalline phases of the treated sediment after 28 days in order to explain the mechanisms responsible for immobilization of the heavy metals under study. The results showed that pH and strength were found to have great influence on metal release. The UCS values of solidified samples at 7, 14 and 28 days exceeded the minimum landfill disposal limits of 0.34N/mm2 (340 kPa). Similarly after 28 days of curing the concentration of the selected heavy metals in the TCLP, SPLP and DIW leaching tests were also either undetected or below the allowable leachability limits. Results have indicated that the partial replacement of cement with RHA in the binder system has increased the strength and reduced leachability of the treated compared to untreated sediment samples.